2020
DOI: 10.2147/jmdh.s269940
|View full text |Cite
|
Sign up to set email alerts
|

<p>Healthcare Worker Experience and the Challenges in Screening for Intimate Partner Violence Among Women Who Use Antiretroviral Therapy and Other Health Services in Wolaita Zone, Ethiopia: A Phenomenological Study</p>

Abstract: Background: Intimate partner violence is a crime against humanity. This study aimed to explore the experiences and challenges in screening for intimate partner violence among women who use antiretroviral therapy and other health services in Wolaita Zone in Ethiopia. Methods: A descriptive phenomenological qualitative study design was used, and 16 in-depth interviews were conducted with healthcare workers from 19 health facilities who were providing healthcare services in Wolaita Zone. We selected participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 17 publications
(30 reference statements)
2
15
0
Order By: Relevance
“…Most of these studies show that male partners are the main perpetrators of violence against women and physical violence is one of the most frequently reported forms of violence, which is used to inflict pain (Aboagye et al, 2021; Coll et al, 2020; Cruz et al, 2014; INE e MISAU, 2013; Russell et al, 2014; Shamu et al, 2016). The experiences of health workers also indicate a high number of women presenting with wounds, bruises and scars due to IPV (Lawoko et al, 2013; Meskele et al, 2020). We note, however, that women in this study mainly reported physical and sexual violence, with less emphasis on psychological abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies show that male partners are the main perpetrators of violence against women and physical violence is one of the most frequently reported forms of violence, which is used to inflict pain (Aboagye et al, 2021; Coll et al, 2020; Cruz et al, 2014; INE e MISAU, 2013; Russell et al, 2014; Shamu et al, 2016). The experiences of health workers also indicate a high number of women presenting with wounds, bruises and scars due to IPV (Lawoko et al, 2013; Meskele et al, 2020). We note, however, that women in this study mainly reported physical and sexual violence, with less emphasis on psychological abuse.…”
Section: Discussionmentioning
confidence: 99%
“…In Mozambique, as in many other African countries, the services to address IPV are not specific for young women (Governo de Mocambique, 2012; Lawoko et al, 2013; Meskele et al, 2020). The opportunity for those young women in dating or in occasional relationships or those initiating relationships and experiencing IPV to seek help may be limited.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Known challenges are the service providers’ attitudes, perceptions, and lack of knowledge about GBV. 10 , 22 , 23 GBV screening is also impacted by the absence of GBV-specific training in national medical curricula, awareness of the scope of the GBV problem, and not knowing what to do when women disclose GBV impact HCWs level of confidence in asking question. 10 , 24–26 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, a poor referral system between different support services, and a lack of specific GBV clinics to support integrated services has been reported as a barrier to GBV screening. 10 , 22 , 25 GBV-supporting networks are reported to be ineffective and uncoordinated, which may discourage GBV survivors from seeking solutions. 10 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies have reported lack of guidelines, organizational policies, separate recording, and registration, limited facilitated IPV training for providers, lack of referral network and specific referral systems or follow-up and delay in medico-legal reports for IPV victims were health system barriers that affected provider readiness in managing IPV [17,21,22].…”
Section: Introductionmentioning
confidence: 99%